FRI0216 Therapeutic Education and Functional Readaptation in Obese Patients on A Waiting List for Total Knee Replacement. A Case-Control Study. (10th June 2014) - Nuñez, M.; Nuñez, E.; Lozano, L.; Sastre, S.; Saulό, A.; Segur, J.M.; Alemany, X.; Macule, F.; Suso, S.
Abstract : Background: Studies show patients with knee osteoarthritis (OA) on waiting list for total knee replacement (TKR) underused conservative treatment, did not adhere to clinical guidelines on knee OA management, and potentially had earlier surgery and a higher risk of revisions. Therapeutic education and functional readaptation (TEFR) plus conventional therapy in waiting list patients improved function and adherence. TKR patients are often obese, negatively influencing TKR results, many patients are dissatisfied after TKR, and around 14% of TKR are inappropriate. Objectives: To compare whether TEFR plus conventional therapy improves health outcomes in obese patients (body mass index [BMI ≥35]) with knee OA and a control group receiving conventional therapy only at entry to a TKR waiting list and after 12 months. Methods: Case-control study with 18 months follow-up. TERF patients received conventional medical and surgical treatment plus TEFR (n=59). TERF combined individualized and group visits (4 months before TKR) based on cognitive learning theories, social change approaches and active teaching strategies. Controls were matched for age, sex, BMI and total WOMAC score (n=59). Sociodemographic, clinical and intra- and postoperative surgical data were collected. The health status was measured using the disease-specific WOMAC questionnaire. Evaluations: baseline, 12 months post TKR, and 4 months post baseline in the TEFR group. Results: TEFR group : 56 female, mean age 68.8 (SD 7.8) years, BMI 40.1 (SD 3.8) WOMAC total index 60.5 (17.2). At 4 months there were significant improvements in all WOMAC dimensions (p<0.001). At 4 months, 10 patients refused surgery due to improvement. At 12 months after TKR (n=49) there was a significant improvement compared with scores at 4 months (p<0.001) and baseline with a mean reduction of 34.95 (95%CI 29.8–40.1) points in total WOMAC score. Control group : 56 female, mean age 70.2 (SD 6.6) years, BMI 40.2 (SD 3.6) and total WOMAC score 63.3 (SD 17.3). At 12 months, there was a significant improvement in all dimensions (p<0.001) with a reduction in total WOMAC score of 32.7 (95%CI 26.5-38.8). Between-group comparison showed no significant differences at baseline. 12 months after TKR, no significant differences were found except for the WOMAC function dimension (mean score 19.5 (SD 10.4) in the TEFR group and 30.98 (SD20.5) in controls (p<0.001). Patients who refused TKR had no significant differences at baseline but were younger and had a better health status (mean age 65.4 (SD 9.6) years, BMI 40.9 (SD 3.3) and WOMAC score 54.5 (18.7). After 4 months of TEFR they showed mean improvements in all WOMAC dimensions of >16 points, which was maintained until study completion. Conclusions: Patients receiving TEFR plus conventional therapy had better health outcomes due to improvements in function showing TEFR to be effective. In 10 who rejected TKR, the health status improved, suggesting the utility of specific programmes to treat patients before inclusion on waiting lists. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5193